2015
DOI: 10.1007/s12325-015-0208-2
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing Hypoglycemia and Weight Gain with Intensive Glucose Control: Potential Benefits of a New Combination Therapy (IDegLira)

Abstract: Due to the progressive nature of type 2 diabetes (T2D), the majority of patients require increasing levels of therapy to achieve and maintain good glycemic control. At present, once patients become uncontrolled on oral antidiabetic therapies, the two primary treatment options are glucagon-like peptide-1 receptor agonists (GLP-1RAs) or basal insulin, although earlier use of GLP-1RAs has also been advocated. While both of these drug classes have proven efficacy in treating T2D, there can be limitations to their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Recent clinical studies have shown that combinations of GLP-1 agonists and insulin are a rational treatment choice, as the inclusion of the GLP-1 agonist improves antihyperglycaemic efficacy while limiting the weight gain and hypoglycaemia associated with insulin. 17,18 Hence, the efficacy of liraglutide should both be judged across patients with different stages of diabetes, as well as judged at the level of the individual patient against other available therapeutic options at their stage of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical studies have shown that combinations of GLP-1 agonists and insulin are a rational treatment choice, as the inclusion of the GLP-1 agonist improves antihyperglycaemic efficacy while limiting the weight gain and hypoglycaemia associated with insulin. 17,18 Hence, the efficacy of liraglutide should both be judged across patients with different stages of diabetes, as well as judged at the level of the individual patient against other available therapeutic options at their stage of disease.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, it was estimated that 863,106 people in the Czech Republic were living with diagnosed diabetes (patients with impaired glucose tolerance not included), of whom 84% had type 2 diabetes mellitus (T2DM) [2]. Good glycemic control is crucial to reduce the incidence of diabetes-related complications and, consequently, the clinical and economic burden associated with diabetes [3, 4]. In the Czech Republic, lifestyle changes and metformin therapy are recommended as first-line therapy for patients with T2DM [5].…”
Section: Introductionmentioning
confidence: 99%
“…New therapies with improved safety and convenience are needed to address this problem. Some progress has been made to address this problem, such as the development and use of IDegLira (Morales and Merker, 2015).…”
Section: Introductionmentioning
confidence: 99%